Adolescent Brain Development and Progressive Legal Responsibility in the Latin American Context - Mercurio, Ezequiel; García-López, Eric; Morales-Quintero, Luz Anyela; Llamas, Nicolás E.; Marinaro, José Ángel; Muñoz, José M. (Frontiers in Psychology, 2020)
In this article, we analyze the contributions of neuroscience to the development of the adolescent brain and shed additional light on the minimum age of criminal responsibility in the context of Latin America. In neurobiology, maturity is perceived to be complex because the brain’s temporal development process is not uniform across all its regions. This has important consequences for adolescents’ behavior; in their search for the acceptance of their peers, they are more vulnerable to pressure and more sensitive to stress than adults. Their affectivity is more unstable, and they show signs of low tolerance to frustration and important emotional reactivity, with a decrease in the capacity to self-regulate. Consequently, risky behavior presents itself more frequently during adolescence, and behaviors that transgress norms and social conventions typically peak between the ages of 17 and 19 years. However, only a small percentage of young offenders escalate their behavior to committing crimes during adulthood. In comparative law, there are considerable differences in Latin American countries’ legal dispositions regarding the minimum age of criminal responsibility; Brazil, Costa Rica, and Ecuador regard the age of criminal responsibility to be 12 years, while Argentina accepts this to be 16 years. From a legal viewpoint, however, the debate about the minimum age of criminal responsibility is connected to other circumstances that, because they are still at a developmental stage, are attributed to adolescents’ rights in their decision-making and understanding of autonomy (e.g., the minimum ages for voting, alcohol consumption, and medical consent). We argue that research on the development of the adolescent brain does not provide definitive answers about the exact age required for different juridical purposes. Nonetheless, the current state of knowledge does allow for reflection on the development and maturation of adolescents and the implications for considering them criminally responsible. It also validates demands for a system that provides adolescents with greater protection and that favors their healthy integral development. In any case, although a specific minimum age is not evident, this study is disposed not to recommend lowering the age of criminal responsibility, but rather increasing it.